2018
DOI: 10.31234/osf.io/3jwtq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

To act fast or to bide time? Adaptive exploration under competitive pressure

Abstract: Competitive pressure affects a wide spectrum of decisions under uncertainty. It forces the individual to balance the value of gathering more information about the quality of potential choice alternatives against the risk that competitors will act first and claim the best options. Although this tradeoff between competition and exploration has long been recognized, little is known about how people adapt their exploration of uncertain options when facing competitive pressure. We examined how competitive pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This type of decision-making process requires less time in negotiation and communication (Robert Baum and Wally, 2003), resulting in faster decisions. In an expansionary economy phase, making quick decisions can help in launching more and new products, and consequently, help in gaining market share (Markant et al, 2018). For example, Judge and Miller (1991) found that decision-making speed strongly correlates with sales growth and profitability in the biotechnology industry.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…This type of decision-making process requires less time in negotiation and communication (Robert Baum and Wally, 2003), resulting in faster decisions. In an expansionary economy phase, making quick decisions can help in launching more and new products, and consequently, help in gaining market share (Markant et al, 2018). For example, Judge and Miller (1991) found that decision-making speed strongly correlates with sales growth and profitability in the biotechnology industry.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Only few studies have started to investigate the role of competitive pressure in people's decisions from experience while simultaneously taking into account additional aspects of the choice ecology Markant et al, 2019). The present approach is the first to systematically vary the statistical properties of choice environments, thus specifically permitting to test the prediction that competitive pressure is a driver of efficiency.…”
Section: The Optimistic View: Competition As a Driver Of Efficiencymentioning
confidence: 99%
“…As in many real-life settings, it may be exactly this combination of a limited choice set (i.e., "only one room left at this price") and the presence of competitors that triggers agency-related concerns. Future research could further examine how competitive search unfolds in other configurations, such as when more choice options are available Markant et al (2019) as well as when more competitors are present -which would, however, substantially complicate the analysis of search and choice in the context of a cost-benefit framework.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
See 1 more Smart Citation